A systematic Review on the effect of physical activity on pupils’ motor skills - Olumuyiwa Ayobami Ajayi (Indonesian Journal of Sport Management, 2022)
This study aimed at examining the effect of physical activity on pupils’ motor skills in Asa Local Government Area. Pretest-posttest quasi experimental research design was adopted in this study. The population of this study comprised of all pupils’ in Asa Local Government Area. Simple random sampling technique was used to select one public and one private primary school in Asa Local Government Area. Sample size contained 57 pupils’ which were gotten from two intact classes. The schools were grouped into one experimental and one control group. The experimental group was exposed to physical activities while the control was exposed to the conventional method of teaching. Physical activity was the treatment while placebo was given to control group. The instrument was validated by experts in Human Kinetics department and reliably tested at (r=0.91). Descriptive statistics of mean, standard deviation and percentage were used to analyze demographic information and Analysis of Covariates (ANCOVA) was used to analyze the research hypotheses. The findings of the study revealed that there was significant difference in the development of pupils using physical activities. Based on the findings of this study, the study concludes that physical activities improve motor skills development of pupils. It was recommended among others that pupils should be encouraged by teachers and school on physical activities and school owners should provide necessary equipment to foster physical activities in schools.